US and EU secure vaccine production on home soil - Jan Malek; Melissa Newham; Jo Seldeslachts; Marcel Wieting (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
The deployment of a safe and effective vaccine for Covid-19 will be central to lifting containment measures. In a bid to speed up vaccine deployment, governments are entering into 'Advance Purchase Agreements' (APAs) with vaccine companies to secure access to vaccine doses. We document and compare the vaccine procurement strategies of the US and the EU. Most notably, we find that both the US and the EU only secure vaccine doses from developers whose (contracted) production facilities are based in US or EU territory, respectively. Securing vaccine production on home soil is crucial in a crisis because of the ability of governments to implement export restrictions; vaccines produced in a different jurisdiction may be blocked from exiting the region. Thus, only governments who can secure local production will be able to provide a vaccine quickly.
Keywords: 330